ANALISIS KUALITATIF TERHADAP PENGARUH TRANSAKSI DIGITAL BANKING TERHADAP FEE BASED INCOME DI SEKTOR PERBANKAN - Syahrani, Sefiza; Fasa, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
This research aims to analyze the influence of digital banking transactions on fee based income in the banking sector. In the era of digital transformation, banks face the challenge of adapting to technological innovations that can increase fee-based income. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews and observations at several banks that implement digital banking services. The research results show that digital banking transactions significantly contribute to increasing fee-based income, with factors such as the number of transactions and customer satisfaction being the main keys. The prospects of this research show that further development in digital banking services can increase bank competitiveness and provide added value for customers.